Persistent Model Biases in the CMIP6 Representation of Stratospheric Polar Vortex Variability. Issue 12 (22nd June 2021) - Hall, Richard J.; Mitchell, Daniel M.; Seviour, William J. M.; Wright, Corwin J.
Abstract: Sudden stratospheric warmings (SSWs) can have major impact on surface wintertime weather, especially at mid‐high latitudes. We do not yet have a complete understanding of why some of these events influence our weather more than others, but one factor may be the dynamical nature of the SSW; whether it involves a split or a displacement of the polar vortex, and one way to explore this is through comprehensive climate models. Here, we analyze the stratospheric dynamics of SSWs within models from the sixth Coupled Model Intercomparison Project (CMIP6). All CMIP6 models simulate SSWs to some degree, although we find a persistent bias in the relative underrepresentation of split vortex events. When comparing with CMIP5 models, large biases persist despite significant model improvements in resolution and in representing atmospheric processes. We show that the simulated displacement frequency is strongly related to climatological lower stratospheric eddy heat flux. The split frequency, on the other hand, is not related to lower stratospheric eddy heat flux, but is strongly related to both the vortex geometry (aspect ratio) and lower stratospheric zonal winds. This suggests that those models with a large positive bias in zonal winds may inhibit the propagation of zonal wavenumber 2 planetary waves from the troposphere, which are associated with split events. Our results suggest how future model development may address these longstanding biases. Plain Language Summary: In winter, the polar stratosphere is very cold and surrounded by strong westerly winds, known as the stratospheric polar vortex. This vortex can be disrupted, and the polar stratosphere can warm by as much as 40K in a few days. This is known as a sudden stratospheric warming (SSW). These events are characterized as splits, when the vortex splits into two smaller vortices, or displacements, where the vortex is shifted away from the pole. Since SSWs were discovered in the 1950s, there have been roughly equal numbers of splits and displacements. Climate models simulate SSWs, although they usually simulate more displacements than splits. We investigate the reasons for this model bias. Those models which have too‐circular a vortex tend to simulate too few split events. In addition, atmospheric waves from the surface can disrupt the vortex. If the lower stratospheric westerly winds are too strong in a model, some of these waves that favor split events can be filtered out. On the other hand, models with a vortex that is on average centered too far from the pole tends to simulate too few displacement events. Our results are useful for supporting the future development of climate models. Key Points: The frequency of split SSW events in particular is underrepresented in most models compared to reanalysis Biases in split SSW frequency are associated with the climatological vortex aspect ratio and lower stratospheric wind representation Biases in displacement SSW frequency are associated primarily with the climatological vortex location